THE STUDY OF SOCIO-PSYCHOLOGICAL ASPECTS OF THE FRUSTRATING STATE OF MILITARY PERSONNEL - Butayev Ulughbek Abdusattorovich (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, the causes, factors, and problems of the origin of frustrating situations that occur in military personnel are extensively covered by data studied in socio-psychologically psychodiagnostic assessment of sergeants on Q-sorting questionnaire. The reliability of the data collected in the research process is explained, first of all, by the fact that the testers who participated in the study were selected accordingly, the practical results obtained were scientifically substantiated, world psychology used techniques and questionnaires that were conducted many times from experiments, the practical results obtained were based on the theoretical side.